Research on a tunable monochromatic X-rays source in (5∼40) keV. (March 2022) - Guo, Siming; Jiang, Zheng; Wu, Jinjie; Qie, Xiaoyu; Yu, Tao; Guo, Kaiyue; Hou, Dongjie; Huang, Jianwei
Abstract: The monochromatic X-rays produced by Bragg diffraction has the advantage of continuously adjustable energy, which is the preferred scheme to realize the monochromatic X-rays. In order to establish a (5–40) keV monochromatic X-rays facility, the Bragg diffraction of crystal monochromator is studied. The position of the emitted X-rays beam is required to remain unchanged when the Bragg angle is adjusted to accurately calibrate the detection efficiency. The monochromatic X-rays calibration facility is mainly composed of an X-rays tube, diffraction crystal and synchronous rotating device, which could cover the energy range of (5–40) keV. A new mechanical structure was invented to realize the linkage between crystal and X-rays tube. When the Bragg angle of crystal is adjusted at θ, the X-ray source will rotate at 2θ angle, and the position of the monochromatic X-rays beam will remain unchanged. Based on the Monte Carlo simulation program, the geometric structure model of silicon drift detector is established. The structure of the detector is optimized according to the experimental conditions and the material size of the shell, window and crystal of the detector. The accurate and reliable detector model is obtained. The response of the detector to different energy under the parallel X-rays source is calculated, and the detection efficiency curve is obtained. The detection efficiency is calibrated by using standard radiation source to ensure the accuracy of photon flux measurement. The energy range, flux, monochromaticity and spot distribution of the monochromatic X-rays radiation device are measured. Highlights: The monochromatic X-rays facility is composed of an X-ray tube, diffraction crystal and synchronous rotating device. The emitted X-rays beam is required to remain unchanged when the angle is adjusted to calibrate the detection efficiency. When the angle is adjusted at θ, the source will rotate at 2θ angle, the position of the X-rays beam will remain unchanged.